2015
DOI: 10.1186/s12934-015-0385-3
|View full text |Cite
|
Sign up to set email alerts
|

In vivo polyester immobilized sortase for tagless protein purification

Abstract: BackgroundLaboratory scale recombinant protein production and purification techniques are often complicated, involving multiple chromatography steps and specialized equipment and reagents. Here it was demonstrated that recombinant proteins can be expressed as covalently immobilized to the surface of polyester (polyhydroxyalkanoate, PHA) beads in vivo in Escherichia coli by genetically fusing them to a polyester synthase gene (phaC). The insertion of a self-cleaving module, a modified sortase A (SrtA) from Stap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…2D; Supplementary Fig. 5) also enable us to estimate that this equates to ~37 pmoles of GFP being released from ~302,000 AL-PHA beads, which is within the range of previous granule surface protein coverage estimates [65,68]. Whilst, as expected, the supernatant fluorescence levels of control biosensor samples were unchanged by AcTEV (10…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…2D; Supplementary Fig. 5) also enable us to estimate that this equates to ~37 pmoles of GFP being released from ~302,000 AL-PHA beads, which is within the range of previous granule surface protein coverage estimates [65,68]. Whilst, as expected, the supernatant fluorescence levels of control biosensor samples were unchanged by AcTEV (10…”
Section: Resultssupporting
confidence: 78%
“…Interestingly, these PHAs beads can also be functionalised in vivo with engineered fusion proteins, which decorate the materials surfaces [64]. Such functionalised PHAs beads have enabled novel protein purification strategies [65], as well as the development of PHAs-based vaccines [66]. Indeed, insights from previous studies have demonstrated that post purification, PhaC remains bound to the bead surface [67].…”
Section: Resultsmentioning
confidence: 99%
“…The properties and functionalities of the PHAs depend on their monomer composition: whereas scl‐PHAs show thermoplastic properties similar to polypropylene, mcl‐PHAs display elastic features similar to rubber or elastomer (Keshavarz and Roy, ; Park et al ., ). Applications of PHAs in the industry are widespread, ranging from the manufacturing of packages and covers to the generation of enantiomeric pure chemicals (Philip et al ., ) or as protein immobilization supports (Draper and Rehm, ; Dinjaski and Prieto, ; Hay et al ., ). Of significant relevance is the implementation of PHAs in the biomedical discipline, especially supported by the recent FDA approval for P(4HB) to be used as suture material (Tepha Inc., MA, USA).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, streptavidin displayed on the granule surface was demonstrated to participate in the biotinylation of proteins and in the purification of biotinylated DNA [57]. A modified sortase A (self-cleaving module) and its five-amino acid recognition sequence, too, were fused to synthase and displayed on granules [58]. Such engineered granules have provided a simple protein production and purification method.…”
Section: Fabrications For Pha Granulesmentioning
confidence: 98%